Pengembangan Media 2D Board Sains Pada Pembelajaran IPA Untuk Meningkatkan Hasil Belajar Siswa Kels VII MTs NW Rumbuk - gilang ramadan, riski (Cocos Bio, 2024)
This innovative research aim to develop and test the effectives of 2D science board learning media in improving students understanding of the digestuve system and organ systems in humans, this study used the R&D ( Research and Development) method from Borg and Gall. Data collection techniques used observation, validation and testing, where the target of this study was class VII MTs/ Equivalent. The results of this study indicate that this media is interesting and interactive and effective in achieving learning objectivs, expert validation and student responses respond possitevly to atractive and interactive visual display and can improve student learning outcomes, which of course supports the conclusion that 2D science board media is a teaching and that is proven to be aeffective interactive and practical when applied to science learning Keywords: Learning Media, 2D Science Board , Research and Development, Science Learning